2020
DOI: 10.1073/pnas.2001812117
|View full text |Cite
|
Sign up to set email alerts
|

NORs on human acrocentric chromosome p-arms are active by default and can associate with nucleoli independently of rDNA

Abstract: Nucleoli, the sites of ribosome biogenesis and the largest structures in human nuclei, form around nucleolar organizer regions (NORs) comprising ribosomal DNA (rDNA) arrays. NORs are located on the p-arms of the five human acrocentric chromosomes. Defining the rules of engagement between these p-arms and nucleoli takes on added significance as describing the three-dimensional organization of the human genome represents a major research goal. Here we used fluorescent in situ hybridization (FISH) and immuno-FISH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 41 publications
(69 reference statements)
6
35
0
Order By: Relevance
“…Mol Syndromol 2021;12:1-11 DOI: 10.1159/000512676 the 47S rDNA arrays located on the short arms clustering in the nucleolus are transcriptionally active, this clustering is independent of the number of rDNA blocks [van Sluis et al, 2020]. The rDNA operons are transcribed by RNA polymerase I [Yuan et al, 2007].…”
Section: Impact Of Robertsonian Translocationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mol Syndromol 2021;12:1-11 DOI: 10.1159/000512676 the 47S rDNA arrays located on the short arms clustering in the nucleolus are transcriptionally active, this clustering is independent of the number of rDNA blocks [van Sluis et al, 2020]. The rDNA operons are transcribed by RNA polymerase I [Yuan et al, 2007].…”
Section: Impact Of Robertsonian Translocationsmentioning
confidence: 99%
“…Yet, the pseudodiploid male fibrosarcoma cell line HT1080, the highly aneuploid female cervical carcinoma cell line HeLa, and the female bone osteosarcoma epithelial cell line U2OS all carry RTs [van Sluis et al, 2020]. HeLa cells are defective for a TP53-encoded 3′→5′ exonuclease and U2OS cells are defective for the alpha thalassemia/mental retardation X-linked (ATRX) gene.…”
Section: Impact Of Robertsonian Translocationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher NORs count usually an indication for cellular proliferation, which is considered as an initial step towards neoplastic progression [17]. These nuclear regions are associated with rDNA which usually indicates cellular activity, mostly related to cell division [18].…”
Section: Discussionmentioning
confidence: 99%
“…AgNORs count method was widely used in oral exfoliative cytology particularly among cigarette smokers to predict early cellular proliferative activity indicating neoplastic change [ 19 ], but its use for lung cytology is scarce [ 20 ]. It was reported that cellular proliferative quantified by AgNORs might play a substantial role in the early detection and diagnosis of premalignant and malignant lesions in the absence of clinical manifestations [ 21 ].…”
Section: Discussionmentioning
confidence: 99%